Do we have friendly services to meet the needs of young women exposed to intimate partner violence in the Madrid region? - Eva Durán‐Martín; Carmen Vives‐Cases; Laura Otero‐García; Esther Castellanos‐Torres; Belen Sanz‐Barbero (Wiley, 2022)
Abstract Introduction Women experiencing intimate partner violence (IPV) do not tend to go very frequently to formal support services. The objective of this study is to identify barriers related to the accessibility, acceptability, equity, appropriateness and effectiveness of IPV services from the perspective of the professionals working in the IPV public services. Methods A qualitative study was carried out in the Madrid region based on 13 semi‐structured interviews of young women who had survived IPV as well as 17 interviews with professionals. A thematic content analysis was performed, guided by the dimensions proposed by the World Health Organization (WHO) for friendly services for young people. Results From the perspective of the young women and professionals, barriers were identified for all the dimensions of the WHO's friendly services for young people: accessibility: lack of information and support from the social setting, scarce dissemination of the services, economic cost, non‐adapted schedules, inadequate locations or lack of services in settings close to young people; acceptability: lack of protocols to guarantee confidentiality, lack of speed in the provision of services or their referral, unwelcoming environments or unsympathetic professional malpractice; equity: discriminatory professional attitudes towards groups with different social status and lack of protocols to ensure the care of these groups; appropriateness: unmet needs and lack of multidisciplinary teams; and effectiveness: shortage of time, resources, competent professionals, protocols and coordination. Conclusions Strategies are needed to make the necessary changes to promote friendly services for the care of young people exposed to IPV. Additionally, it must be emphasized that resources are needed to raise awareness and disseminate IPV services, as well as to train professionals in this area. Patient or Public Contribution This paper is based on professionals' perspectives of public IPV‐related services of different areas such as Psychology, Social Work, Nursing, Psychiatry, Social Education and young women exposed to IPV. They either work in the public administration at the local, regional or state level or in NGOs in Spain.